Behavior and shear strength of SFRC beams without stirrups: proposed model and parametric analyses - Debella, Leticia Col; de Sousa, Alex Micael Dantas [UNESP]; de Resende, Thomás Lima; Pieralisi, Ricardo (Elsevier, 2024)
One of the challenges in using steel fiber reinforced concrete (SFRC) in structural members is the lack of simple and physically sound expressions to predict its mechanical properties. For instance, most expressions to predict the shear strength of SFRC beams use semi-empirical-based expressions or iterative mechanical models. Therefore, such equations usually fail to evaluate the combined effect of steel fibers with other concrete shear-carrying mechanisms or require extensive calculations to overcome this limitation. Aiming to fill this gap, this paper presents a simple closed-form solution to evaluate the shear capacity of SFRC with conventional steel reinforcement based on the main shear transfer mechanisms and supported by experimental measurements through digital image correlation (DIC). The model was devised theoretically, based on concepts previously established in the literature, without introducing purely empirical coefficients. The robustness of the proposed model was checked (i) against an experimental program on which the main shear-carrying mechanisms were measured and (ii) on a database of 158 beams reported in the literature that failed due to shear. Finally, a parametric analysis was developed to discuss the key parameters of the shear strength of SFRC beams. The proposed model showed good accuracy compared to the experimental results and other analytical approaches, and it excels due to its simple and physically sound background.
Keywords: Analytical model; DIC; Mechanisms; SFRC; Shear